2020
DOI: 10.1002/ange.202004192
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Lead Vacancy and Water Rationalizes the Puzzle of Charge Carrier Lifetimes in CH3NH3PbI3: Time‐Domain Ab Initio Analysis

Abstract: The perovskite CH3NH3PbI3 excited‐state lifetimes exhibit conflicting experimental results under humid environments. Using ab initio nonadiabatic (NA) molecular dynamics, we demonstrate that the interplay between lead vacancy and water can rationalize the puzzle. The lead vacancy reduces NA coupling by localizing holes, slowing electron–hole recombination. By creating a deep electron trap state, the coexistence of a neutral lead vacancy and water molecules enhances NA coupling, accelerating charge recombinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Further study indicates the interplay between the water molecules and lead vacancy in HOIPs significantly accelerates the nonradiative recombination. 15 On the all-inorganic perovskite side, dozens of experiments have also shown that the stability and optoelectronic characteristics of inorganic perovskite solar cells (PSCs) depend on the humidity conditions. Meloni and co-authors demonstrated that exposing the CsPbBr 3 perovskite films to humidity can enhance the crystallinity of films and improve device performance.…”
mentioning
confidence: 99%
“…Further study indicates the interplay between the water molecules and lead vacancy in HOIPs significantly accelerates the nonradiative recombination. 15 On the all-inorganic perovskite side, dozens of experiments have also shown that the stability and optoelectronic characteristics of inorganic perovskite solar cells (PSCs) depend on the humidity conditions. Meloni and co-authors demonstrated that exposing the CsPbBr 3 perovskite films to humidity can enhance the crystallinity of films and improve device performance.…”
mentioning
confidence: 99%